Anatomical and Topographical Relations between the Posterior Lens Capsule and the Intraocular Lens in Pseudoexfoliation Syndrome - E. V. Egorova (Oftalʹmologiâ)
Purpose — to study the relations between the posterior capsule (PC) and intraocular lens (IOL) after cataract surgery in pseudoexfoliation syndrome (PEX).Patients and methods. We examined 46 eyes of 37 patients with PEX who underwent a standard and uncomplicated phacoemulsification. The age of patients was 60–94 years. Postoperative period ranged from 1 day to 10 years. An optical coherence tomography (OCT) (RTVue XR Avanti, “Optovue”) was used to image the IOL-PC space in early and late postoperative period.Results. In the first days full contact PC-IOL was not observed in any case. The maximum of space PC-IOL was noted on the first day postoperatively. Posterior capsule had a wavy or folded profile on the scans. In the next two weeks we observed a decrease of the distances between posterior capsule and IOL. After 1 month we noted the formation of capsular bend around optic edge, the full adhesion of posterior capsule to IOL was not detected. In the late postoperative period the fibroplastic and proliferative capsular changes with secondary discontact PC-IOL was noted. Primary inadhesion of a posterior capsule to IOL was recorded in half of the cases.и. High resolution OCT was suitable for quantitative analysis of IOL-PC space. Involution changes in structures of anterior segment in the eyes with PEX had a role in closure of the IOL-PC space. Complete adhesion of posterior capsule to IOL was not observed in the majority of eyes with PEX.